The association between temporal measures of swallowing with penetration and aspiration in patients with dysphagia: A meta-analysis - Furkima, Ana Maria (2019)
INTRODUCTION: Temporal features of swallowing physiology vary with age in healthy normals and have the potential to impact swallow safety and efficiency in patients with dysphagia. We conducted a meta-analysis to assess the relation between temporal features of swallowing with penetration, aspiration and residue in adult patients with dysphagia regardless of etiology. METHODS: Operational definitions of relevant terms were defined a priori. A search of 5 databases was conducted to November 2016 without restriction to language. Two independent raters reviewed abstracts and full articles, with discrepancies resolved by consensus. All accepted articles advanced to data extraction and critical appraisal according to Cochrane standards. Analysis of pooled data compared measures between groups. RESULTS: Of the 11 articles accepted, the temporal measures used in three or more studies were grouped into morphofunctional categories: bolus transit time; pharyngeal response time; laryngeal closure time; and upper esophageal opening time. Across all selected articles, definitions varied for abnormal swallow and only 4 articles reported rater blinding and reliability for measures related to timing. Pooled data identified two main findings: a. longer pharyngeal response time was associated with penetration and/or aspiration (MD = 0.40 95% CI 0.59-0.22), and longer upper esophageal opening duration was associated with only aspiration (PAS ≥ 6) (MD = 0.09 95% CI 0.16-0,02). No studies were found that related temporal measures and residue. CONCLUSION: Our pooled findings identified an association of two temporal measures with penetration and/or aspiration but none with residue. The current evidence remains limited due to the heterogeneity across studies in how swallow measures were operationalized. Future work with a standardized and reproducible approach is direly needed.